Joining Guerrilla groups in Colombia: Individual motivations and processes for entering a violent organization (2007)
Using in-depth interviews with forty-two former Colombian guerrillas from three groups, M-19, EPL, and CRS, this article identifies eleven different motivations for joining these organizations. Special attention is given to the recruitment process as well as the role that religion, family, and acquaintances play in subjects' decisions to join these subversive organizations. Finally, Matza's three-stage model is used to investigate the process of joining these groups. Findings emphasize the importance of factors such as social interactions, government repression level, and insurgent group resources and goals in the subjects' decision to join these groups.